Effect of portable negative pressure units on expelled aerosols in the operating room environment. Issue 7 (1st April 2022) - Popovic, Marko; Beathe, Jonathan; Gbaje, Ejiro; Sharp, Marla; Memtsoudis, Stavros G
Abstract : Introduction: Spontaneously breathing patients undergoing procedures under regional anesthesia can expose operating room personnel to infectious agents. The use of localized negative pressure within proximity of a patient's airway is expected to reduce the amount of bioaerosols dispersed particularly for anesthesia staff who are frequently near the patient's airway. Methods: In the experiment, aerosols were produced using a polydisperse aerosol generator with nebulized saline. A portable negative pressure unit was set up at set distances of 10 cm and 30 cm with the aim of reducing aerosol particle counts detected by a laser-based particle counter. Results: Without the portable negative pressure unit, the median concentration of 0.5 µm aerosols detected was 3128 (1533, 22832) particles/ft 3 /min. With the portable negative pressure unit 10 cm and 30 cm from the site of aerosol emittance, the median concentration compared with background concentration was −0.5 (−8, 8) particles/ft 3 /min and 398 (89, 1749) particles/ft 3 /min, respectively. Conclusions: For particle concentrations of 0.5 µm, 0.7 µm, and 1.0 µm a significant amount of aerosol reduction was observed (p<0.001). Further experiments are warranted to assess the safety of staff when encountering a potentially infectious patient in the operating room.